Dampak Cemas Terhadap Kesehatan Reproduksi Pekerja Wanita Usia Subur - Puteri, Febyona Jolest; Febriawati, Henni; Emi Kosvianti; Nopia Wati; Weti (Citra Delima Scientific journal of Citra Internasional Institute, 2025)
Based on figures from the Central Statistics Agency, the percentage of women as professional workers will decrease by 1.34% in 2022. Previously it was 49.99% to 48.65%. Workers with a high depression/anxiety index were 100% and an average of 89.5% experienced reproductive health problems. The aim of this research is to determine the impact of depression/anxiety on reproductive health in female workers of childbearing age. Women of Childbearing Age (WUS) with an age range of 15-49 years. This research method is Mixed Methods with a strategy that is embedded concurrently and uses gradual quantitative-qualitative data analysis. The sample in this study was 10 women of childbearing age. Based on the results of the Self-Reporting Questionnaire (SRQ)-20 test conducted on a sample of 10 female workers of childbearing age, the results showed that 3 respondents experienced depression/anxiety. The results of in-depth interviews (In-Depth Interviews) show that depression/anxiety has an impact on the reproductive health of female workers of childbearing age, such as irregular menstrual cycles and pregnancy disorders. The conclusion of this study is that there is a relationship between depression/anxiety and the reproductive health of women of childbearing age. The researcher's advice to all women is to keep trying to do positive things when experiencing depression/anxiety and to consult further with experts.